Red yeast rice extract improves lipid metabolism by modulating gut microbiota in high-fat diet mice - Hu, Peng; Zhang, Li; Hu, Hongtao; Wang, Di; Chen, Jia; Xiao, Jinghuan; Wu, Hang; Qi, Luming; Qin, Kaihua; Zuo, Xiaohong; Li, Juan (Frontiers in Pharmacology, 2025)
As a traditional food-medicine dual-purpose substance, red yeast rice (RYR) has gained wide attention for its lipid-lowering activity. However, existing studies mainly focus on the liver-targeted effects of statin-like components, with limited systematic insights into its lipid metabolism regulation via gut microbiota. This study combines high-fat diet (HFD)-induced hyperlipidemia mouse models, 16S rRNA gene sequencing, untargeted metabolomics, and fecal microbiota transplantation (FMT) to investigate the potential of RYR extract in improving lipid metabolism through gut microbiota modulation. The results showed that RYR extract significantly improved body weight, serum total cholesterol (TC), triglycerides (TG), low-density lipoprotein cholesterol (LDL-C) levels, and hepatic lipid deposition in HFD-fed mice. Additionally, RYR extract effectively restored the intestinal structural damage and enhanced intestinal barrier function. 16S rRNA revealed that RYR extract significantly modulated the gut microbiota, increasing the abundance of beneficial bacteria such as Bifidobacterium and restoring the ratio of Firmicutes to Bacteroidota. Metabolomics analysis revealed that RYR extract significantly modulated the gut microbiota-derived metabolites, particularly in the tryptophan metabolism and phenylalanine metabolism. FMT experiments showed that the fecal microbiota from RYR-treated group obviously improved the blood lipid levels, liver pathology, and intestinal function in HFD-fed mice. These results suggest that RYR extract improves lipid metabolism through the modulation of gut microbiota and related metabolic pathways, which provides new insights into the mechanism research of RYR’s lipid-lowering effect.